2004
DOI: 10.1080/13556210410001717088
|View full text |Cite
|
Sign up to set email alerts
|

Increased sibling mortality in children with fetal alcohol syndrome

Abstract: We compared the rate of all‐cause mortality in siblings of children diagnosed with fetal alcohol syndrome (FAS) with the siblings of matched controls. The siblings of children with FAS had increased mortality (11.4%) compared with matched controls (2.0%), a 530% increase in mortality. The age of death in case siblings deaths occurred later (between 1 day and 7 years) compared with the controls (1 day to 4 years) [odds ratio (OR) = 2.4 (0.4 ‐ 15.6)]. Siblings of children with FAS had increased risk of death due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 12 publications
1
32
0
Order By: Relevance
“…20 Our literature search found no direct evidence of a link with fetal alcohol syndrome, although siblings of these infants have been shown to have a 10-fold higher risk of SIDS. 21 Exposure to maternal hard drug use during pregnancy has also been linked with increased risks of allcause infant mortality 22 and SIDS, 23 although the risks are even higher if exposure continues during infancy. 24 While maternal substance misuse may directly affect the baby both before and after birth, the ill effects of exposure to paternal alcohol or drug use are restricted to the latter period.…”
Section: Possible Causal Mechanismsmentioning
confidence: 99%
“…20 Our literature search found no direct evidence of a link with fetal alcohol syndrome, although siblings of these infants have been shown to have a 10-fold higher risk of SIDS. 21 Exposure to maternal hard drug use during pregnancy has also been linked with increased risks of allcause infant mortality 22 and SIDS, 23 although the risks are even higher if exposure continues during infancy. 24 While maternal substance misuse may directly affect the baby both before and after birth, the ill effects of exposure to paternal alcohol or drug use are restricted to the latter period.…”
Section: Possible Causal Mechanismsmentioning
confidence: 99%
“…Siblings of children with FAS have been found to have an increased mortality rate. 3,4,13,14 Three siblings (2 cases and 1 control) died of SIDS. SIDS has been associated with prenatal alcohol exposure and binge drinking in the first trimester in Northern Plains American Indians.…”
Section: Discussionmentioning
confidence: 99%
“…A diagnosis of FASD is associated with increased risk of death for affected people and their siblings (even when the sibling FASD status is unknown) [21] [22]. In populations of children with an FASD, recent reports suggests a 5% -6% mortality risk [10] [21] [22] [26]. Several reports have also demonstrated increased rates of mortality in mothers of children with FAS [10] [27]- [30].…”
Section: Discussionmentioning
confidence: 99%
“…In previous reports we have suggested that a context of prenatal alcohol exposure should be considered in all infant and childhood deaths [25]. A diagnosis of FASD is associated with increased risk of death for affected people and their siblings (even when the sibling FASD status is unknown) [21] [22]. In populations of children with an FASD, recent reports suggests a 5% -6% mortality risk [10] [21] [22] [26].…”
Section: Discussionmentioning
confidence: 99%